Aplikasi Campuran Kompos TKKS Dengan Abu Boiler dan Pupuk Nitrogen Terhadap Beberapa Komponen Hasil dan Kandungan Protein Beras - Sukandar '; Nelvia '; Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT This research aims to determine the effect of compost mixture of palm oil empty fruit bunches with boiler ash and nitrogen fertilizer on some yield components and protein content of rice. Research was conducted from Desember 2012 to March 2013 and located at PulauRambai Village Kampar Timur District, Kampar Regency. Research Methode used completely randomized design experiment consisting of two factors, the first factor is the aplicationcompost and boiler ash which consists of 4 levels that are (not compost and boiler ash, 5 ton compost + 500 kg/ha boiler ash, 5 ton compost + 750 kg/ha boiler ash, and 5 ton compost + 1000 kg/ha boiler ash). The second factor is the aplication of nitrogen fertilizer which in consisted by 2 levels that are (100 kg N/ha and 200 kg N/ha). In a research obtained 8 combinations repeated 3 time. Research result indicate that the aplication of 5 tons of compost have mixed 1000 kg/ha boiler ash and its follow application fertilizer 200 kg N/ha can increase plant height, plant number of grains, pithy grains percentage, and protein content of rice. Keyword :Compost, boiler ash, nitrogen, Rice